THE ROLE OF FREE ECONOMIC ZONES IN THE ECONOMIC GROWTH OF UZBEKISTAN A CASE STUDY OF THE SOUTH KOREAN EXPERIENCE - Norimov, Islomiddin (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In the era of the globalizing world, when states are becoming more and more dependent on each other, Uzbekistan, which continues the transition to the principles of a market economy, has also entered this path. One of the main conditions for ensuring stable economic growth in individual territories is an increase in investment activity based on the widespread involvement of domestic and foreign investors. To accomplish this task and an intensive transition to the principles of an open market economy, there is a need to create free economic zones (FEZ). There are already 23 free economic zones in Uzbekistan, 21 of which specialize in industry, 2 in agriculture, where industrial goods are produced for the domestic market and for export. However, the study revealed that there are several problems in the free economic zones in Uzbekistan that need to be addressed. To verify these objectives correlation, and regression analysis conducted. The analysis revealed that out of six factors, the two factors of FEZ export and FEZ investment are the major factors that directly impacted economic growth